The experience of living to an extreme age: a meta-ethnography - Toye, F; Jenkins, C; Barker, KL (SAGE Publications, 2019)
Advances in health care mean that we can now treat diseases that once cut lives short. However, the increase in life expectancy has not been matched by improvements in quality of life. The World Health Organization warns us that all countries should prepare to meet the challenges of an aging population and this is integral to the United Nations 2030 Agenda for Sustainable Development. This may require a shift in attitude toward aging. We aimed to use meta-ethnography to explore the experience of adults living beyond the age of 80. Our conceptual model illuminates the phenomenon of connection in older age and reflects on the paradox of time: ephemeral, yet interminable. Our findings encourage us to reflect on the influence of enlightenment philosophies that underpin the desire for autonomy at all costs. Our study challenges the stereotypes of old age and has the potential to influence people’s perspectives toward aging.